Dimerização quimioseletiva de vinilarenos catalisada por tribrometo de índio - Andrade, Fabiano Molinos de (2004)
This work describes our first results on the use of indium(III) salts as catalysts of oligo-polimerization processes of olefins. The first class of olefins which were tested was vinylarenes under the catalytic influence of indium tribromide. Styrene slowly polymerizes in the presence of the catalyst. β-, tri- and tetra-Substituted vinylarenes were inert under the experimental conditions. The catalyst is chemioseletive for dimerization of α-methylstyrene and its derivatives. It imposes a rigorous chemical control of dimeric products. Acyclic terminal olefins dimers or cyclic dimers containing the indane skeleton were, alternatively, obtained depending on the substituents attached to the arylic moiety of the vinylarenes. [...]